Evolutionary Structural Optimization as Tool in Finding Strut-and-tie-models for Designing Reinforced Concrete Deep Beam. (2015) - Hardjasaputra, Harianto
Abstract: Strut-and-Tie models are well-known worldwide as valuable tool in designing D-Regions of Reinforced Concrete members. It has been adopted in many Concrete Structural Codes in many countries. Recently strut-and-tie-models have been included in Indonesia Concrete Structural Code (SNI-03-2847-2012). In this paper, it will be shown how a Strut-and-Tie Model can be developed for various structural concrete deep beams using Evolutionary Structural Optimization. As a tool for this study the author used Bi-Directional Evolutionary Structural Optimization (BESO2D) computer programs, developed by X. Huang and Y.M. Xie[1] . Three tested concrete beams with small, medium, and large opening[2] will be taken as the case study. It will be shown the optimal topology of a plane stress of continuum structures produced from BESO2D can be taken as the basic strut-and-tie-model. For design process the best strut-and-tie-model can be delivered from the optimal topology structure only with the deep knowledge of the basic load transfer from loading to support point